THE IMPACT OF SOCIAL MEDIA MARKETING ON CONSUMER BUYING BEHAVIOUR: THEORETICAL ASPECT - SOKHATSKA, Olena; SIDDHARTH, SIDDHARTH (Journal of European Economy, 2019)
This research studies the impact of social media marketing on consumer buying behaviour. The aim of this research is to explore how social interactive tools have an influence on buying decision process and how others’ productrelated opinions collected from social and digital environment are influential on buying decisions in different markets. This project sought to assess the impact of social media on the decision making process among the consumers. The study’s general objective was to establish the impact of social media on consumer’s decision making process among the consumers across different level of the society. The study was guided by the following specific objectives: to find out how social media influences the pre-purchase stage in buyer’s decision process, to determine how social media influences the purchase stage in buyer’s decision process, and to determine how social media influences the post purchase stage in buyer’s decision process. The study aims at integration of social media marketing communication tools and consistency in the message communicated via social media tools. In addition, it aims to have conclusive recommendations for further study which should include involvement in marketing research with a core purpose of delivering per consumer needs, as well as gaining an understanding of trending social media activities so as to meet demands of changing technological world. JEL: D03, E03.